Clays and Clay Minerals, Vol. 56, No. 2, 259–271, 2008. - Hamdi, Noureddine; Srasra, Ezzedine (The Clay Minerals Society, 2008)
Clayey soils are essential materials used to reduce hydraulic conductivity and pollutant migration, common at sites of waste disposal. This study investigates the possible use of a Tunisian soil as a lining material for disposal sites for acidic-fluoride wastes. A permeability test on a waste-solution sample (pH = 2.7) obtained from a disposal site in southern Tunisia was conducted over a period of about 2 years. The test results show that the permeability decreased with time until stabilized at 8.33610-11 m/s. After the permeability test, the samples retrieved from the permeameter show a degradation state which varied with the thickness of the specimen. These samples can be classified into three zones (Z1: unaffected, Z2: moderately affected; and Z3: extensively affected). Physicochemical characterization of the three samples (Z1, Z2, and Z3), and of the original argillaceous soil, was by X-ray diffraction, Fourier transform infrared spectroscopy, differential thermal and thermal gravimetric analysis, 29Si and 27Al nuclear magnetic resonance, and N2-adsorption techniques. The original sample consists essentially of palygorskite, kaolinite, and quartz. Sample Z3 underwent complete dissolution of kaolinite which supports the precipitation of fluoroaluminate and the appearance of an X-ray amorphous silica phase. In samples Z1 and Z2, the soil adsorbs fluoride at a rate of ~68.5 mg/g and is highly resistant to acidic attack.
Interaction Of Aqueous Acidic-fluoride Waste With Natural Tunisian Soil.
Clays and Clay Minerals, Vol. 56, No. 2, 259–271, 2008. Interaction Of Aqueous Acidic-fluoride Waste With Natural Tunisian Soil. Noureddine Hamdi; Ezzedine Srasra. DOI: 10.1346/CCMN.2008.0560209. Copyright © 2008, The Clay Minerals Society.
Keywords: Periodicals; Geology; Acidic-fluorideWaste Storage; Clay; DTA-TG; FTIR; Permeability; 29Si and 27Al NMR; XRD